AUF1 regulation of coding and noncoding RNA. (13th September 2016) - White, Elizabeth J.F.; Matsangos, Aerielle E.; Wilson, Gerald M.
Abstract : AUF1 is a family of four RNA‐binding proteins (RBPs) generated by alternative pre‐messenger RNA (pre-mRNA) splicing, with canonical roles in controlling the stability and/or translation of mRNA targets based on recognition of AU‐rich sequences within mRNA 3′ untranslated regions. However, recent studies identifying AUF1 target sites across the transcriptome have revealed that these canonical functions are but a subset of its roles in posttranscriptional regulation of gene expression. In this review, we describe recent developments in our understanding of the RNA‐binding properties of AUF1 together with their biochemical implications and roles in directing mRNA decay and translation. This is then followed by a survey of newly discovered activities for AUF1 proteins in control of miRNA synthesis and function, including miRNA assembly into microRNA (miRNA)‐loaded RNA‐induced silencing complexes (miRISCs), miRISC targeting to mRNA substrates, interplay with an expanding network of other cellular RBPs, and reciprocal regulatory relationships between miRNA and AUF1 synthesis. Finally, we discuss recently reported relationships between AUF1 and long noncoding RNAs and regulatory roles on viral RNA substrates. Cumulatively, these findings have significantly expanded our appreciation of the scope and diversity of AUF1 functions in the cell, and are prompting an exciting array of new questions moving forward. WIREs RNA 2017, 8:e1393. doi: 10.1002/wrna.1393 This article is categorized under: RNA Interactions with Proteins and Other Molecules > Protein–RNA Recognition RNA Turnover and Surveillance > Regulation of RNA Stability Regulatory RNAs/RNAi/Riboswitches > Regulatory RNAs Abstract : AUF1 enhances loading of select miRNAs into RISCs and can also regulate miRISC access to mRNA substrates.